1998
DOI: 10.1074/jbc.273.4.2312
|View full text |Cite
|
Sign up to set email alerts
|

The Axonally Secreted Serine Proteinase Inhibitor, Neuroserpin, Inhibits Plasminogen Activators and Plasmin but Not Thrombin

Abstract: Neuroserpin is an axonally secreted serine proteinase inhibitor that is expressed in neurons during embryogenesis and in the adult nervous system. To identify target proteinases, we used a eucaryotic expression system based on the mouse myeloma cell line J558L and vectors including a promoter from an Ig--variable region, an Ig-enhancer, and the exon encoding the Igconstant region (C) and produced recombinant neuroserpin as a wild-type protein or as a fusion protein with C. We investigated the capability of rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
118
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(120 citation statements)
references
References 72 publications
2
118
0
Order By: Relevance
“…However, there is evidence that cleaved NS could result from dissociation of the complex. Osterwalder and colleagues (13,19) have shown the dissociation of the complex between tPA and chicken neuroserpin, which has Ͼ80% homology to human neuroserpin and an identical reactive center loop. Our investigations show conclusively that the generation of the reactive center loop-cleaved species of NS was mainly because of the dissociation of the NS⅐tPA complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is evidence that cleaved NS could result from dissociation of the complex. Osterwalder and colleagues (13,19) have shown the dissociation of the complex between tPA and chicken neuroserpin, which has Ͼ80% homology to human neuroserpin and an identical reactive center loop. Our investigations show conclusively that the generation of the reactive center loop-cleaved species of NS was mainly because of the dissociation of the NS⅐tPA complex.…”
Section: Discussionmentioning
confidence: 99%
“…Following docking, the reactive loop is cleaved, and the proteinase is inhibited by translocation over 70 Å to the lower pole of the inhibitor (16,17). The most probable target for neuroserpin is tissue plasminogen activator (tPA) (13,18,19), and it has been suggested that neuroserpintPA interactions play an important role in regulating neuronal and synaptic plasticity and memory (20 -27).…”
mentioning
confidence: 99%
“…This serpin is secreted from the axonal growth cones of the central and peripheral nervous system, where it inhibits the enzyme tissue plasminogen activator (1)(2)(3)(4)(5). The expression pattern of neuroserpin and its in vitro inhibitory activity implicate this serpin in regulating axonal growth, reducing seizure activity, controlling damage in cerebral infarction, and regulating emotional behavior and memory (6 -10).…”
mentioning
confidence: 99%
“…It has been shown previously that neuroserpin can inhibit both tPA and uPA in vivo (Yepes et al, 2000) and that it is neuronally expressed and axonally secreted (Osterwalder et al, 1998). Because PAs are also secreted proteins that function in the extracellular matrix, neuroserpin provides a tool for interfering with PA activity under pathological conditions.…”
Section: Resultsmentioning
confidence: 99%